Is city of residence a factor differentiating sitting time in adolescents? - Roberval Pizano; Christianne de Faria Coelho Ravagnani; Robert Weaver; Maria Sylvia Vitalle (Revista Brasileira de Atividade Física e Saúde)
The aim of this cross-sectional study was to examine the association between city of residence and other factors related to sitting time in adolescents. Students (n = 1,089), between 14 and 18 years, completed self-reported questionnaires to collect data about sitting time, general fitness, physical education and sport participation, socio-economic stratum and householder ́s education in Botucatu (SP), Cáceres (MT) and São Paulo (SP). The choice of municipalities occurred for convenience and the selection of schools and students was performed randomly. Multi-level mixed linear regression models were used to estimate the relationship between the independent variables and sitting time (min.day-1) during weekdays and weekend days. Hierarchal models were estimated to account for the nested nature of student within schools. Regarding cities of residence, there was no association with sitting time on both weekday (São Paulo, β = 36.87, CI: 25.6; 233.62 and Cáceres, β = 66.94, CI: 22.1; 156.01) and weekend (São Paulo, β = 104.01, CI: 64.5;138.20 and Cáceres, β = 90.23, CI: 33.2; 213.64), when compared to Botucatu. Socio economic indicators were related to sitting time in different ways considering week or weekend. Students with higher householder education degrees had more sitting time on weekdays. On weekend students in higher levels of socioeconomic stratum presented less sitting time. Adolescents with very good perception of general fitness had -65.29 minutes of sitting time on weekday and -70.1 minutes of sitting time on weekend. In the present study, city of residence was not related to sitting time in adolescents. However, other factors such as gender, socioeconomic stratum and educational status, participation in sports and physical education and perceptions of fitness were related to students sitting time.